Assessment of genetically modified oilseed rape GT73 for renewal authorisation under Regulation (EC) No 1829/2003 (application EFSA‐GMO‐RX‐026/1). (6th October 2022) - ,; Mullins, Ewen; Bresson, Jean‐Louis; Dalmay, Tamas; Dewhurst, Ian Crawford; Epstein, Michelle M; Firbank, Leslie George; Guerche, Philippe; Hejatko, Jan; Moreno, Francisco Javier; Naegeli, Hanspeter; Nogué, Fabien; et al.
Abstract: Following the submission of application EFSA‐GMO‐RX‐026/1 under Regulation (EC) No 1829/2003 from Bayer Agriculture BV on behalf of Bayer CropScience LP, the Panel on Genetically Modified Organisms of EFSA was asked to deliver a scientific risk assessment on the data submitted in the context of the renewal of authorisation application for foods and food ingredients containing, consisting of, or produced from oilseed rape GT73 with the exception of isolated seed protein, and feed produced from this GM oilseed rape, excluding cultivation in the EU. The data received in the context of this renewal application contained post‐market environmental monitoring reports, a systematic search and evaluation of literature, updated bioinformatic analyses, and a search for additional documents or studies performed by or on behalf of the applicant. The GMO Panel assessed these data for possible new hazards, modified exposure or new scientific uncertainties identified during the authorisation period and not previously assessed in the context of the original application. Under the assumption that the DNA sequences of the events in oilseed rape GT73 considered for renewal are identical to the sequences of the originally assessed event, the GMO Panel concludes that there is no evidence in renewal application EFSA‐GMO‐RX‐026/1 for new hazards, modified exposure or scientific uncertainties that would change the conclusions of the original risk assessment on oilseed rape GT73.